P-OGC21 Patient perspectives on symptoms of importance and preferences for follow-up after major upper gastro-intestinal cancer surgery. (16th December 2021) - Pucher, Philip; Coombes, Annie; Evans, Orla; Taylor, Joanna; Moore, Jonathan; White, Annabelle; Lagergren, Jesper; Baker, Cara; Kelly, Mark; Kelly, Mark; Gossage, James; Dunn, Jason; et al.
Abstract: Background: Long-lasting symptoms and reductions in quality of life are common after oesophago-gastric surgery. Post-operative follow-up has traditionally focussed on tumour recurrence and survival, but there is a growing need to also identify and treat functional sequelae to improve patients' recovery. Methods: An electronic survey was circulated via a British national charity for patients undergoing oesophago-gastric surgery and their families. Patients were asked about post-operative symptoms they deemed important to their quality of life, as well as satisfaction and preferences for post-operative follow-up. Differences between satisfied and dissatisfied patients with reference to follow-up were assessed. Results: Among 362 respondents with a median follow-up of 58 months since surgery (range 3-412), 36 different symptoms were reported as being important to recovery and quality of life after surgery, with a median 13 symptoms per patient. Most (84%) respondents indicated satisfaction with follow-up. Unsatisfied patients were more likely to have received shorter follow-up than 5 years (27% among unsatisfied patient vs. 60% among satisfied patients, p < 0.001and were less likely to have seen a dietitian as part of routine follow-up (37% vs. 58%, p = 0.005). Conclusions: This patient survey highlights preferences with regard to follow-up after oesophago-gastrectomy. Longer follow-up and dietician involvement improved patient satisfaction. Patients reported being concerned by a large number of gastrointestinal and non-gastrointestinal symptoms, highlighting the need for multidisciplinary input and a consensus on how to manage the poly-symptomatic patient.